Effect of Various Irrigating Devices on the Removal of Two Different Forms of Calcium Hydroxide from Internal Resorption Cavities - Nima Mousavi Nasab Mobarakeh; Afsaneh Taheri; Hadi Rahmanian; Dana Jafarpour; Sareh Rahmanian (International Journal of Dentistry)
The present study aimed to investigate the efficiency of passive ultrasonic irrigation (PUI), EndoActivator (EA), standard needle irrigation (SNI), and XP-endo Finisher files in removing pure calcium hydroxide (pCH) and injectable CH from in vitro root resorption cavities. Using a rotary system, the root canals of 116 extracted single rooted teeth were prepared. Imitated internal resorption cavities were then created in root halves. The specimens were divided into two groups according to the form of CH (n = 58): (I) pCH; (II) injectable CH. The teeth of each group were randomly divided into six subgroups: negative control (n = 5), positive control (n = 5), PUI (n = 12), XP-endo Finisher (n = 12), EA (n = 12), and SNI (n = 12). The root canals were irrigated using NaOCl and EDTA and split longitudinally, and both halves were evaluated with a stereomicroscope. Kruskal–Wallis and Mann–Whitney U tests were used to analyze data. The present results revealed that PUI completely removed pCH in 79% and injectable CH in 70.8% of the internal resorption cavities which was significantly higher than other methods (p<0.05). There was no statically significant difference between different forms of CH in terms of CH removal (p=0.918). The PUI technique was observed as the most efficient method of P-CH and injectable CH removal from a replicated internal resorption cavity. Finally, according to the findings, different forms of CH were comparable in terms of CH removal.